Analisis Kinerja Account Representative Dalam Mengatasi Masalah Kepatuhan dan Penagihan Pajak Terhadap Wajib Pajak Badan di KPP Pratama Jambi Telanaipura - Evi Nurhayati; Haviz Taufik; Eka Julianti Efris Saputri; Liona Efrina (Pusat Riset dan Inovasi Nasional, 2026)
This study is motivated by the important role of Account Representatives (AR) and tax collection in supporting the improvement of corporate taxpayers’ compliance. However, the compliance level at KPP Pratama Jambi Telanaipura still faces challenges, making it necessary to analyze how these two factors influence taxpayers’ compliance behavior. The purpose of this research is to examine the effect of AR performance, tax collection, and both simultaneously on corporate taxpayers’ compliance. The research method applied is quantitative with an associative approach. Data were collected through questionnaires distributed to corporate taxpayers at KPP Pratama Jambi Telanaipura and analyzed using multiple linear regression with the assistance of SPSS. The findings indicate that AR performance has a positive but not significant effect on corporate taxpayers’ compliance, while tax collection has a positive and significant influence. When considered together, both variables contribute to improving compliance, although other external factors beyond this research are also likely to affect taxpayer behavior